Cervical Cancer screening attitudes and beliefs of Malaysian women who have never had a pap smear: a qualitative study - Wong, L.P.; Wong, Y.L.; Low, W.Y.; Khoo, E.M.; Shuib, R. (2008)
Background: Attitudes toward cervical cancer and participation in early detection and screening services are well known to be profoundly affected by cultural beliefs and norms. Purpose: This study explored the attitudes and sociocultural beliefs on cervical cancer screening among Malaysian women. Method: In this qualitative study, in-depth interviews were conducted with 20 Malaysian women, ages 21 to 56 years, who have never had a Papanicolaou (Pap) smear. Results: Respondents generally showed a lack of knowledge about cervical cancer screening using Pap smear, and the need for early detection for cervical cancer. Many believed the Pap smear was a diagnostic test for cervical cancer, and since they had no symptoms, they did not go for Pap screening. Other main reasons for not doing the screening included lack of awareness of Pap smear indications and benefits, perceived low susceptibility to cervical cancer, and embarrassment. Other reasons for not being screened were related to fear of pain, misconceptions about cervical cancer, fatalistic attitude, and undervaluation of own health needs versus those of the family. Conclusion: Women need to be educated about the benefits of cervical cancer screening. Health education, counseling, outreach programs, and community-based interventions are needed to improve the uptake of Pap smear in Malaysia.